Public Art Commissions by Koper/Capodistria Noblemen. The Role of the City Procurators and of University of Padua Graduates in the Construction of Capodistria Cathedral - Seražin, Helena (Acta historiae artis Slovenica, 2022)
The article discusses the role of the Capodistria nobility in public art commissions, using the example of the hitherto little researched municipal office of procurators or advocates of the Cathedral of Capodistria (Procuratore della Fabrica della Cattedrale di Capodistria). The procurators Benvenuto Marquis Gravisi (1679–1746), Alvise Count Tarsia (1697–1774) and Francesco Barbabianca (1695–1753) had the greatest say in the selection of architects and contractors and thus significantly influenced the final appearance of Capodistria Cathedral, which was rebuilt in the first half of the 18th century. When selecting architects such as Giorgio Massari (1687–1766) and Domenico Schiavi (1718–1795), they made use of the advice of educated people from Koper such as Girolamo Marquis Gravisi (1720–1812) and Gian Rinaldo Count Carli (1720–1795) as well as the connections which they had made during their studies at the University of Padua or as members of academies. Thus, in 1748–1749, the procurators were able to consult the then leading authority in architecture in the Republic of Venice, Giovanni Marquis Poleni (1683–1761), professor of experimental physics at the University of Padua, in connection with the reconstruction of the choir of the Cathedral of Capodistria.